Tajikistan Contemporary Poetry Themes - Gholam Abas Nafisi; Mohammad Ali Davood Abadi Farahani; Ali Sar Yaghoubi (Journal of Language and Literature, 2019)
Tajik poetry deviated from its mainstream with the victory of the communist revolution. The imposition of Russian language and the new communist literature made Tajik poetry to take influence from the works of Russian romantic poets and to have new themes. Meanwhile, it benefited from the ancient Persian poets and one can see the rhetorical figures such as metaphor, simile, conflict, pun, ?h?m, proverb, husn-i ta'lil (good reason), imagery and paradox in the works of Tajik poets. Additionally, B?del's poem has also had a clear influence on the poetry of some contemporary poets. Tajik poetry is very close to the informal language of the people, and in these poems, we encounter words that are specific to the Tajik dialect. The first Persian she'r-e now (new poetry) in Central Asia was written by Sadriddin Ayni.In Tajik poetry, we occasionally encounter with recurrences, the nostalgia of the missed glory, the oppression of the nation, and the unwanted fate of their ancestors. In these poems, the rely on emotion and content, and the epic and passionate tone prevail other poetic performances. The present study gives a general overview of the poetry of some Tajik poets.